Deciphering the role of claudins in lung cancer - Arabi, Tarek Ziad; Alkattan, Wael; Osman, Nadine Ashraf; Sabbah, Belal Nedal; Ashraf, Nader; Ouban, Abderrahman (Frontiers in Oncology, 2024)
Lung cancer remains a major global health challenge, characterized by aggressive malignancy and poor prognostic outcomes. This review article focuses on the pivotal role of claudins, a family of tight junction proteins, in the pathophysiology of lung cancer. Claudins are integral to maintaining epithelial barrier function and cellular polarity, yet they are intricately involved in the progression and metastasis of lung cancer. The aberrant expression of claudins has been observed across various histological subtypes of lung cancer, indicating their potential as diagnostic and prognostic biomarkers. Specifically, claudins such as claudin-1, -2, -3, -4, and -7 exhibit diverse expression patterns that correlate with tumor aggressiveness, patient survival rates, and response to therapies. Inflammation and cytokine modulation significantly influence claudin expression, affecting tumor microenvironment dynamics and cancer progression. This review also highlights the therapeutic implications of targeting claudins, particularly in cases resistant to conventional treatments. Recent advances in this area suggest that claudin-modulating agents may enhance the efficacy of existing therapies and offer new avenues for targeted interventions. By integrating the latest research, this article aims to provide a comprehensive understanding of claudin’s roles in lung cancer and encourages further clinical trials to explore claudin-targeting therapies. This could pave the way for more effective management strategies, improving outcomes for lung cancer patients.